Ultrashort pulse generation with an erbium-doped fiber laser ring cavity based on a copper oxide saturable absorber - Sadeq, Sinan Abdulhameed; Harun, Sulaiman Wadi; Al-Janabi, Abdul Hadi (Optical Society of America, 2018)
A soliton mode-locked erbium-doped fiber (EDF) laser has been experimentally demonstrated using copper oxide (CuO) thin film as a saturable absorber (SA). The dispersion of the EDF cavity including the CuO-SA was balanced by a suitable length of single-mode fiber (SMF). The fabricated CuO-SA has 3.5% modulation depth and 3.3 MW∕cm2 saturation intensity. The mode-locked train pulses have 1.7 ps pulse width and 983 kHz repetition rate, while the pulse energy and output power are 1.29 nJ and 1.27 mW, respectively, at maximum pump power of 159 mW. These results indicate that the CuO thin film is a good SA candidate for a fiber laser operating at a low pump power. To the best of our knowledge, this is the first demonstration of a CuO-SA-based mode-locked fiber laser.